HUBUNGAN PERSEPSI REMAJA MENGENAI WACANA KENAIKAN HARGA ROKOK TERHADAP KEBIASAAN MEROKOK PADA REMAJA - Aina " Handayani; Ari Pristiana Dewi; Ganis " Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Cigarrete  is one of the tobacco products that are intended to be burned and to be inhaled. This study aims to determine the correlation of adolescent’s perception about the discourses of increasing cigarette price on adolescent’s smoking habit in SMK Muhammadiyah 1 Pekanbaru. This study used a study descriptions correlation design  and cross sectional approach. The study samples are 184 respondents that was taken based on inclusion criteria using stratified random sampling technique. Measuring instrument that used was a structured questionnaire that designed by the researchers to measure adolescent’s  perceptions about discourses of increasing cigarette price against the smoking habit in adolescents. Questionnaire for adolescent’s perception about discourses of increasing cigarette price against the smoking habit in adolescents  have been tested for validity with value (r = 0.467 to 0.890), and have been tested reliability with cronbach alpha value s= 0,813.  Data were analyzed by chi-square test and the result is confirm that there’s a correlation between adolescent’s perception about the discourses of increasing cigarette price on adolescent’s smoking habit with p value (0,014) > a (0,05), based on the results of the study are expected  to students who smoke, to try reduce smoking habit  and to motivate themselves and do positive perseption with the larger strategy and precise if the cigarette price is increasing. Keywords: adolescent’s perception about the discourses of increasing cigarette price,adolescent’s smoking habit